2007
DOI: 10.2214/ajr.07.2805
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 3D Free-Breathing Coronary MR Angiography and 64-MDCT Angiography for Detection of Coronary Stenosis in Patients with High Calcium Scores

Abstract: OBJECTIVE-The objective of our study was to compare the diagnostic performance of coronary MR angiography (MRA) and 64-MDCT angiography (MDCTA) for the detection of significant stenosis (≥ 50%) in patients with high calcium scores. MATERIALS AND METHODS-Eighteenpatients (12 men, six women; mean age, 56 y; age range, 38-77 y) who had at least one calcified plaque with a calcium score of > 100 underwent coronary MRA and conventional coronary angiography (CAG) within 2 weeks of MDCTA. Coronary MRA image quality o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(59 citation statements)
references
References 31 publications
1
57
0
1
Order By: Relevance
“…This is one advantage of whole-heart coronary MRA over multidetector computed tomography (MDCT) of coronary arteries in which a lower HR is often essential for high-quality images. In addition, whole-heart coronary MRA does not require exposure to ionizing radiation or the injection of iodinated contrast material, and high-density calcium does not cause beam-hardening artifacts (15). A recent multicenter study demonstrated that the AUC values of 64-row MDCT angiography for detecting significant coronary artery stenosis are 0.93 and 0.91 in patientand vessel-based analyses, respectively (16).…”
Section: Discussionmentioning
confidence: 99%
“…This is one advantage of whole-heart coronary MRA over multidetector computed tomography (MDCT) of coronary arteries in which a lower HR is often essential for high-quality images. In addition, whole-heart coronary MRA does not require exposure to ionizing radiation or the injection of iodinated contrast material, and high-density calcium does not cause beam-hardening artifacts (15). A recent multicenter study demonstrated that the AUC values of 64-row MDCT angiography for detecting significant coronary artery stenosis are 0.93 and 0.91 in patientand vessel-based analyses, respectively (16).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, optimization of scan coverage from non-enhanced CT scan data is important. In addition, one must be aware that the quality of the CTA is likely to be impaired or nondiagnostic if large quantities of coronary calcium are found on non-enhanced CT. 23,24 Thus as mentioned above, apart from ECG information, we need get the most out of non-enhanced prior to coronary CTA.…”
Section: Discussionmentioning
confidence: 99%
“…130 MDCT has a limitation for visualizing the coronary lumen in segments with calcification, because calcifications cause partial volume effects. 131 It has been reported that the detection rate of stenotic lesions is higher in MDCT than in magnetic resonance coronary angiography (MRCA). 132, 133 MDCT is superior to MRCA in terms of spatial resolution, image quality, imaging time, and ease of operation.…”
Section: Coronary Ct and Mrca 341 Contrast Coronary Ct Angiography mentioning
confidence: 99%